Digital Supply Chain Operation Model for Educational Management in Non-Formal Education in Rural Thailand - Artaphon Chansamut (International Journal of Supply Chain Management, 2023)
The objective of this research  study were to study  and to evaluate digital supply chain operation model for educational management in non-formal education in rural Thailand. The samples in the research study consisted of ten purposively selected experts consisted of three experts on supply chain management, five experts on Digital Technology and two experts on the course. Data were analysed by arithmetic mean and standard deviation. The research findings model seven elements namely main components, Supplier, Manufacturer , Finished product, Customers  Satisfaction and Feedback. The ten experts agree that digital supply chain operation model for educational management in non-formal education in rural Thailand was high suitability that show the model is appropriate and applicable to support the tasks.